Environmental setting of the early irrigation in Oasisamerica: Paleopedological evidences from the alluvial palaeosols in la Playa/Sonoran Desert. (20th May 2019) - Ibarra – Arzave, Georgina; Solleiro-Rebolledo, Elizabeth; Chávez-Vergara, Bruno; Sedov, Sergey; Ortega-Rosas, Carmen; Sanchez, Guadalupe; Gamez, Thanairi; Barceinas-Cruz, Hermenegildo; Ayala, Emmanuel
Abstract: Environmental conditions and human-landscape interaction during the onset of the irrigated agriculture in Oasisamerica are not clear yet. In la Playa site (Sonora, NW Mexico), the evidences of sedentary population, land cultivation, and water management developed after the end of Altithermal period (around 4500 yr BP) include more than 550 archaeological features including hundreds of human cremations and a net of buried artificial channels. These findings were closely associated with several palaeosol levels alternating with sediments within a large alluvial fan. We studied micromorphological features, physical characteristics (color, texture, rock magnetic properties), and composition of organic matter, from three profiles (Maravillas, Zanja, and Cuatro Suelos), to reconstruct pedogenesis and sedimentary environment of the palaeosol sequences. Additional paleoenvironmental information was extracted from pollen assemblages, extracted from the Cuatro Suelos profile. The results pointed to a long period of geomorphic and climatic stability in the early-middle Holocene marked by a well-developed red Cambisol. This period was followed by an unstable interval around 4.5 kyr BP marked by severe erosion of earlier soil profiles and sedimentation of different kind: channel, floodplain, and fluvio-eolian. Later synsedimentary Fluvisols were formed showing signs of predominantly arid pedogenesis, interrupted by occasional flooding; indicators of human impact were also encountered. We conclude that the shift to irrigated agriculture as the main subsistence activity occurred during the period of major climatic and geomorphic fluctuation and then irrigation developed further under dry environment with limited water resources during the Late Holocene.